Surgery for subacromial impingement syndrome and occupational biomechanical risk factors in a 16-year prospective study among male construction workers - Charlotte Lewis; Jens Wahlström; Sebastian Mukka; Per Liv; Bengt Järvholm; Jennie A Jackson (Scandinavian Journal of Work, Environment & Health, 2023)

(untitled)
OBJECTIVE: The aim of this study was to assess the association between occupational biomechanical exposures and the occurrence of surgical treatment for subacromial impingement syndrome (SIS). METHODS: A cohort of 220 295 male constructions workers who participated in a national occupational health surveillance program (1971–1993) were examined prospectively over a 16-year follow-up period (2001–2016) for surgically treated SIS. Worker job title, smoking status, height, weight, and age were registered on health examination. Job titles were mapped to 21 occupational groups based on tasks and training. A job exposure matrix (JEM) was developed with exposure estimates for each occupational group. Surgical cases were determined through linkage with the Swedish national in- and outpatient registers. Poisson regression was used to assess the relative risks (RR) for each biomechanical exposure. RESULTS: The total incidence rate of surgically treated SIS over the 16-year observation period was 201.1 cases per 100 000 person-years. Increased risk was evident for workers exposed to upper-extremity loading (push/pull/lift) (RR 1.45–2.30), high hand grip force (RR 1.47–2.23), using handheld tools (RR 1.52–2.09), frequent work with hands above shoulders (RR 1.62–2.11), static work (RR 1.77–2.26), and hand-arm vibration (RR 1.78–2.13). There was an increased risk for SIS surgery for all occupational groups (construction trades) compared with white-collar workers (RR 1.56–2.61). CONCLUSIONS: Occupational upper-extremity load and posture exposures were associated with increased risk for surgical treatment of SIS, which underlines the need for reducing workplace exposures and early symptom detection in highly exposed occupational groups.